Learning styles of medical students change along the study program: from ‘thinking and watching’ to ‘thinking and doing’ - Bitran, Marcela; Zúñiga, Denisse; Pedrals, Nuria; Padilla, Oslando; Mena, Beltrán (Revue canadienne de l’éducation médicale, 2012)
Background: Most students admitted to medical school are abstract-passive learners. However, as they progress through the program, active learning and concrete interpersonal interactions become crucial for the acquisition of professional competencies. The purpose of this study was to determine if and how medical students' learning styles change during the course of their undergraduate program. Methods: All students admitted to the Pontificia Universidad Católica de Chile (PUC) medical school between 2000 and 2011 (n = 1,290) took the Kolb’s Learning Style Inventory at school entrance. Two years later 627 students took it again, and in the seventh and last year of the program 104 students took it for a third time. The distribution of styles at years 1, 3 and 7, and the mobility of students between styles were analyzed with Bayesian models. Results: Most freshmen (54%) were classified as assimilators (abstract-passive learners); convergers (abstract-active) followed with 26%, whereas divergers (concrete-passive) and accommodators (concrete-active) accounted for 11% and 9%, respectively. By year 3, the styles' distribution remained unchanged but in year 7 convergers outnumbered assimilators (49% vs. 33%). In general, there were no gender-related differences. Discussion: Medical students change their preferred way of learning: they evolve from an abstract-reflexive style to an abstract-active one. This change might represent an adaptation to the curriculum, which evolves from a lecture-based teacher-centered to a problem-based student–centered model.